1983
DOI: 10.1073/pnas.80.16.5047
|View full text |Cite
|
Sign up to set email alerts
|

Long-term growth of human B cells and their use in a microassay for B-cell growth factor.

Abstract: Normal human B lymphocytes, prepared from peripheral venous blood, have been stimulated with intact antiIgM (,u chain specific) bound to an insoluble matrix. The activation event, in a subfraction of human B cells, was associated with subsequent receptivity to the mitogenic effects of exogenously added B-cell growth factor. The ability of the cell population to specifically absorb the B-cell growth factor was dependent upon the time of stimulation with the anti-IgM. Continuous replenishment of the growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
21
0

Year Published

1985
1985
1990
1990

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 18 publications
(16 reference statements)
3
21
0
Order By: Relevance
“…The interrelationships of BSF-1 and I3CGF II in the stimulation of B cells also remain to be elucidated. Since BSF-1 with anti-Ig (presumably mimicking the effects of antigen) is sufficient to cause B cells to synthesize DNA (3,(6)(7)(8), the role of BCGF II is puzzling. Earlier studies had suggested that proliferation and maturation to antibody secretion in B lymphocytes are controlled by different lymphokines (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The interrelationships of BSF-1 and I3CGF II in the stimulation of B cells also remain to be elucidated. Since BSF-1 with anti-Ig (presumably mimicking the effects of antigen) is sufficient to cause B cells to synthesize DNA (3,(6)(7)(8), the role of BCGF II is puzzling. Earlier studies had suggested that proliferation and maturation to antibody secretion in B lymphocytes are controlled by different lymphokines (9).…”
mentioning
confidence: 99%
“…Murine B-cell-stimulating factor type 1 (BSF-1) acts on resting B cells and drives them to a transitional activated state characterized by the expression of high levels of Ia antigens (4,5). In combination with antibodies to surface Ig receptors (anti-Ig), it induces B cells to synthesize DNA (3,(6)(7)(8).…”
mentioning
confidence: 99%
“…In general, the signals for B cells mediated by these factors and antibodies have not been biochemically identified. One of these factors, 12-kDa or low molecular weight B-cell growth factor (LMW-BCGF), produced by lectin-activated T cells, is able to support clonal B-cell proliferation and is a predominant factor affecting B cells (12,21).…”
mentioning
confidence: 99%
“…However, a second signal, complementary to the sIg-mediated signal, is required to drive resting B cells into S phase (4)(5)(6). The complementary or "progression" signal can be provided by a variety of growth factors (y interferon, interleukins 1, 2, and 4, 12-and 60-kDa B-cell growth factors), complement components (C3d), or monoclonal antibodies (mAbs) binding to B-cell receptors (anti-CDw40, anti-CD23, and anti-CD22) (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). In general, the signals for B cells mediated by these factors and antibodies have not been biochemically identified.…”
mentioning
confidence: 99%
“…BCGF activity was selectively enriched ~50-fold after DEAE chromatography and further enriched >100-fold after hydroxylapatite chromatography. BCGF was added to culture wells in unit (U) amounts determined on long-term cultured B cells as previously described (11). The TCGF used was purified, cloned material kindly provided by Cetus Corp., Emeryville, CA (lot No.…”
Section: Methodsmentioning
confidence: 99%